The clinical utility of the behavior rating inventory of executive function in preschool children with a history of perinatal stroke. Issue 3 (3rd July 2022) - Di Lorenzo, Miranda; Desrocher, Mary; Westmacott, Robyn
Abstract: The current study examined the utility of the Behavior Rating Inventory of Executive Function-Preschool Version (BRIEF-P) in capturing emerging deficits in executive function in preschool children with a history of perinatal stroke. Parents and teachers of 55 clinically referred preschool children (3–5 years of age) provided ratings using the BRIEF-P. Both parent ( M = 56.02, p = .001) and teacher ratings ( M = 58.61, p = .002) indicated significant scale elevations for working memory compared to the normative sample, albeit below the clinically elevated range. Parent and teacher ratings were low-to-moderately correlated ( r = .05–.55). Greater deficits in working memory ( r = −.58), inhibition ( r = −.45), and planning/organization ( r = −.51), as rated by teachers, were associated with lower intellectual functioning. Parents' ratings were not associated with intellectual functioning. Further, no neurological or personal characteristics were associated with ratings of executive function. The current study demonstrates children with a history of perinatal stroke are, on average, following a normal trajectory of executive function development according to BRIEF-P ratings. The needs for multi-informant ratings and performance-based measures to comprehensively assess executive functioning in preschoolers with a history of stroke are discussed.